Airport capacity choice under airport-airline vertical arrangements. (October 2016) - Xiao, Yibin; Fu, Xiaowen; Zhang, Anming
Highlights: This study investigates airport-airline vertical arrangements on airport capacity. Capital cost savings lead to higher capacity. Vertical arrangements lead to higher profit for a profit-maximising airport. Vertical arrangements lead to higher welfare for a welfare-maximising airport. Win-win outcomes may be achieved without government intervention. Abstract: This study investigates the effects of airport-airline vertical arrangements on airport capacity choices under demand uncertainty. A multi-stage game is analysed, in which competing airlines contribute to capacity investments and share airport revenues. Our analytical results suggest that for a profit-maximising airport, such a vertical arrangement leads to higher capacity but may not increase its profit, whereas for a welfare-maximising airport, such an arrangement has no effect on capacity or welfare. Capital cost savings brought by airport-airline cooperation, if any, always lead to higher capacity, and to higher profit for a profit-maximising airport and higher welfare for a welfare-maximising airport. Numerical simulations reveal that win-win outcomes may be achieved for an airport and its airlines without government intervention.